ANALYSIS OF TRANSFORMATIONAL LEADERSHIP DIMENSIONS AND THEIR IMPACT ON ORGANIZATIONS: A SYSTEMATIC REVIEW - Ainul Yaqin, Muhammad Khafid; Andi Gani, Abdul Juli; Hermawan, Romy (Erudio Journal of Educational Innovation, 2024)
Every leader in running the organization is unique with different talents. Thus, the organization needs to have talent mapping for the selected structural position. In the workplace, leaders influence the behavior of members, because they are seen as exemplary representatives of the organization and have the authority to evaluate members' performance or make decisions related to their promotion. The leadership literature has developed around four main domains, namely the trait approach, behavioral approach, contingency theory, and inspirational theory. There are many theories of Leadership in both the public and private sectors. One of them is the theory of Transformational Leadership. Transformational leadership is part of the “New Leadership” paradigm which pays more attention to the charismatic and affective elements of leadership. This study uses the Systematic Literature Review method. Systematic research through review is a body of study that focuses on methods of collecting library data, or research whose study subjects are studied using various sources of literature, is the methodology used in this literature. The results of this study indicate that the dimensions in the Transformational Leadership model have their characteristics to be applied in a particular organization, be it public, private, or third-sector organizations or Non-Government Organizations (NGOs). This can be interpreted that the character of leadership that prioritizes an individual approach to subordinates by paying attention to the organizational climate has a major impact on the organization both in the form of the birth of innovations and problem-solving. This paper can be a reference for leaders and managers of an organization in leading its members.